(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study endeavors to bridge a critical research gap by elucidating the ramifications of work-family conflict and its influence on various factors, notably employee performance. In addition to assessing the impacts of perceived supervisor support and emotional exhaustion, our research delves into the intricate association between employee performance and work-family conflict. The study involved 220 participants from the service sector who completed a questionnaire, with data analysis carried out using SmartPLS Version 4. Our data analysis reveals a negative correlation between work-family conflict and employee performance, while employee emotional exhaustion exhibits a positive association with both of these variables. Significantly, the relationship between work-family conflict and employee performance is found to be moderated by perceived supervisor support. It’s worth noting that the measurement of work-family conflict was based on employee responses from a general population within the service industry, which, by its nature, made it challenging to pinpoint specific occupational details. This study underscores the importance of fostering constructive relationships with employees, as positive perceived supervisor support is shown to precede favorable employee relations and enhanced employee performance. The study’s distinctive contribution lies in its exploration of the mediating and moderating roles played by emotional exhaustion and perceived supervisor support in elucidating the intricate link between work-family conflict and employee performance.